Świat do rozbiórki. O męskości w Czeskim Raju Jaroslava Rudiša - Maślanka, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Jaroslav Rudiš is a representative of the middle generation of Czech authors, who in many of his works presents an image of masculinity that is fragile and lost in the face of the changes of the modern world. The subject of this article is an analysis of his novella Český ráj as a literary manifestation of Czech models of masculinity, which in their traditional form are out of step with the changing world, and the defensive attitudes adopted in the face of these changes. Attention is also given to the space in which the work’s action takes place – the decaying men’s sauna in Bohemian Paradise – which turns out to be not only the last outpost of masculinity but also its grotesque metaphor.
A world for demolition. About masculinity in Český Ráj by Jaroslav Rudiš
Keywords: Jaroslav Rudiš; Czech literature; masculinity; crisis of masculinity